Gender and Profession as Modulators in Modification of Stereotypes - Vázquez, Carolina; Martínez, Carmen (Anales de Psicología / Annals of Psychology, 2011)
This paper presents the results of the research about the influence of two variables such as gender and profession in the modification of stereotypes. Starting from the classical models about modification of stereotypes, conversion and subtype, and studies based on crossed categorizations, throughout this research the influence of those factors in the way of how the individual stereotype information is presented, either concentrated or scattered it is analyzed. The stereotype index and the perception of typicality were used as variables for the data analysis. The design of this study is based on a 2 (pro-fession) x 2 (gender) x 2 (style of presentation) model which generates eight experimental conditions. The results of this study show how remarkable are the occupational information and/or the information related to the quality level reached in a specific occupation which is being carried out, in the case of establishing, and consequently modifying, a valued judgement which is going to take place. This factor is more influential than allocating men´s or women´s category to an individual.